2017
DOI: 10.3390/ijms18030620
|View full text |Cite
|
Sign up to set email alerts
|

A Biomedical Investigation of the Hepatoprotective Effect of Radix salviae miltiorrhizae and Network Pharmacology-Based Prediction of the Active Compounds and Molecular Targets

Abstract: Radix salviae miltiorrhizae (Danshen in Chinese), a classic traditional Chinese medicine (TCM) herb, has been used for centuries to treat liver diseases. In this study, the preventive and curative potential of Danshen aqueous extract on acute/chronic alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD) was studied. The in vivo results indicated that Danshen could alleviate hepatic inflammation, fatty degeneration, and haptic fibrogenesis in ALD and NAFLD models. In the aspect of mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 58 publications
0
57
0
Order By: Relevance
“…Antioxidative therapy aiming to prevent the progression of liver injury represents a reasonable means of treatment. Although experimental studies in vitro and in animals are encouraging, only few clinical trials have demonstrated the beneficial effects of anti-oxidants regarding the the prevention of progression of ALD [43,44].…”
Section: Phages In Potential Immunotherapy Of Aldmentioning
confidence: 99%
“…Antioxidative therapy aiming to prevent the progression of liver injury represents a reasonable means of treatment. Although experimental studies in vitro and in animals are encouraging, only few clinical trials have demonstrated the beneficial effects of anti-oxidants regarding the the prevention of progression of ALD [43,44].…”
Section: Phages In Potential Immunotherapy Of Aldmentioning
confidence: 99%
“…After comprehensive screening, all the filtered data were imported into Cytoscape, a professional software package in bioscience research for the analysis of network pharmacology (available online at http://www.cytoscape.org/ ). 116 , 117 The detailed relationships regarding the well-accepted ideology of “multitarget, multidrug” among each factor can be straightforwardly observed in Figure 3 . More specifically, the nodes represent the TCMs-related compounds, refined extracts and biological factors (protein or mRNA).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to have hepatoprotective effects on ethanol-induced oxidative damage in primary culture of rat hepatocytes through its antioxidant activity especially the activities of superoxide dismutase (SOD) and glutathione reductase (Chirdchupunseree & Pramyothin, 2010). Previously, Naaz, Javed, and Abdin (2007) (Han et al, 2008), and chronic hepatitis (Hong et al, 2017). According to Chinese Pharmacopoeia, S. miltiorrhiza is considered to possess slightly cold and bitter properties, enters the heart and liver channels and increases blood flow and scavenges free radicals that decreases cellular damage in patients with ischemic diseases (Sun et al, 2005).…”
Section: G Glabra (Licorice)mentioning
confidence: 99%